Pengaruh Pembelajaran Berbasis Masalah Biologi Pada Aspek Kognitif: Sebuah Meta-Analisis - Mila Karmila; Zaenal Abidin (Peneliti.net, 2022)
Problem based learning (PBL) learning model has a role in improving the quality of students. This study aims to re-analyze the PBL learning model in Biology learning on cognitive aspects or student learning outcomes. This study uses a meta-analysis method with a sample of 15 national and international journals. Based on the results of the analysis, it turns out that the PBL learning model is able to improve biology learning outcomes starting from the lowest 15.03% to the highest 61.76% with an average of 29.34%. By obtaining a strong effect size of 0.97. The most significant increase in the PBL model research was 28.13 in the PBL model learning with LKS and by applying problem solving based learning on certain materials. This shows that the application of the PBL learning model can improve learning outcomes in biology learning